Professionalization of the Finnish voluntary sports sector : case study of the Tennis Club of Jyväskylä 1993-2016 - Tiusanen, Jarno (2018)
Professionalization of sports is an on-going phenomenon. Voluntary sports clubs have been based on the values of amateurism. Recently, the trend of professionalization has had effects on the voluntary sports sector. The main aim of the thesis is to explore, describe, understand, and highlight the development, changes, and challenges of the Tennis Club of Jyväskylä (JTS) while moving towards professionalism from 1993 to 2016. At the end, the goal of the study is to enhance our understanding of the voluntary sports club´s operational environment.